2018
DOI: 10.1146/annurev-pharmtox-010617-052722
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microphysiological Systems to Enhance Safety Assessment in Drug Discovery

Abstract: Enhancing the early detection of new therapies that are likely to carry a safety liability in the context of the intended patient population would provide a major advance in drug discovery. Microphysiological systems (MPS) technology offers an opportunity to support enhanced preclinical to clinical translation through the generation of higher-quality preclinical physiological data. In this review, we highlight this technological opportunity by focusing on key target organs associated with drug safety and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 123 publications
0
76
0
Order By: Relevance
“…In this context, a plethora of multiorgan systems have been presented, in which a organotypic hepatic model is integrated with models of other tissues in perfused devices. However, as these applications are outside of the scope of this review, we refer the interested reader to excellent recent reviews on this matter …”
Section: D Culture Paradigms For Phhmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a plethora of multiorgan systems have been presented, in which a organotypic hepatic model is integrated with models of other tissues in perfused devices. However, as these applications are outside of the scope of this review, we refer the interested reader to excellent recent reviews on this matter …”
Section: D Culture Paradigms For Phhmentioning
confidence: 99%
“…For instance, a longitudinal review of AstraZeneca's small‐molecule drug projects from 2005 to 2010 revealed that overall 29% ( n = 11 out of 38 projects) of projects with low confidence in the preclinical safety profile were closed due to safety issues, whereas none of the compounds with high‐quality safety data was terminated due to safety concerns in the clinics ( n = 0 out of 13) . In light of these findings, it is thus not surprising that much research has focused on the development of preclinical model systems that improve the prediction of hepatotoxic liabilities …”
Section: Applications Of Advanced Primary Human Hepatocyte Culture Momentioning
confidence: 99%
“…Hence, external maturation factors must be applied with great caution when differentiating human pluripotent stem cells . The choice of common medium that balances the critical media component of each organ model is yet to be found . Small number of cells and analyte volume of organoids may hinder analyte detection, thus more sensitive biosensors are needed .…”
Section: Cardiac Organoids Outlookmentioning
confidence: 99%
“…36 The choice of common medium that balances the critical media component of each organ model is yet to be found. 2 Small number of cells and analyte volume of organoids may hinder analyte detection, thus more sensitive biosensors are needed. 2 Furthermore, organoid production reproducibility in terms of size, shape, architecture, cellular composition, and production scalability must be taken into account as additional important factors.…”
Section: Cardiac Organoids Outlookmentioning
confidence: 99%
“…Such microphysiological systems can create Organs-on-Chips and provide novel ways to assess pharmacokinetics, pharmacodynamics, and drug-drug and drug-toxicant interactions. Progress in the creation, validation, and utilization of such systems is reviewed in the articles by Prantil-Baun et al (6) and Ewart et al (7).…”
mentioning
confidence: 99%